2023
DOI: 10.1038/s41563-023-01698-8
|View full text |Cite
|
Sign up to set email alerts
|

Task-adaptive physical reservoir computing

Oscar Lee,
Tianyi Wei,
Kilian D. Stenning
et al.

Abstract: Reservoir computing is a neuromorphic architecture that may offer viable solutions to the growing energy costs of machine learning. In software-based machine learning, computing performance can be readily reconfigured to suit different computational tasks by tuning hyperparameters. This critical functionality is missing in ‘physical’ reservoir computing schemes that exploit nonlinear and history-dependent responses of physical systems for data processing. Here we overcome this issue with a ‘task-adaptive’ appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…While the biophysical origin of the restoration of the missing fundamental continues to be a subject of debate, it has been suggested that it can be explained by nonlinear and chaotic effects [17]. Nonlinear processes in biological neural systems have also motivated research on artificial neural networks that exploit the nonlinear properties of diverse mathematical models and physical systems [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…While the biophysical origin of the restoration of the missing fundamental continues to be a subject of debate, it has been suggested that it can be explained by nonlinear and chaotic effects [17]. Nonlinear processes in biological neural systems have also motivated research on artificial neural networks that exploit the nonlinear properties of diverse mathematical models and physical systems [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Although software simulated reservoirs offer enough flexibility to implement such task-dependent adaptive rules, doing the same in physical RC poses a significant challenge. However, recently adaptive reservoirs have also been implemented in physical systems by [ 36 ]. By adapting the thermodynamical phase space of the physical substrate, the same reservoir could be optimized for multiple tasks.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, similarly to the efficiency of the brain of some insects, which has a low number of neurons compared with a human brain, RC systems require just several thousands of neurons to undertake certain tasks more efficiently than a high-performance workstation computer running sophisticated software [36,38]. This property is ideally suitable for the development of AI systems for mobile platforms, where the control unit must consume low power while delivering practicable machine learning, vision and sensing capabilities in a real-time regime [71].…”
Section: Traditional Reservoir Computing Approachmentioning
confidence: 99%